Traumatic brain injury and mental fatique: effects on executive control - Fry, Jessica Dawn (My University, 2009)
The present study was directed at an examination of the executive control of behaviour in both an organically compromised population and in an organically uncompromised population. It was tested whether behavioural manifestations may be linked to compromised executive control. This study also aimed to answer the question as to whether fatigue, as measured by a subjective questionnaire, negatively impacted on executive control. Executive control refers to the ability to sustain attentional capacity as required to regulate perceptual and motor processes in order to facilitate the inductive reasoning required to respond in an adaptive way to changing task demands (Baddeley & Logie, 1999, as cited in van der Linden, Frese & Meijman, 2003). It was operationalised as decreased cognitive flexibility and increased perseveration as measured by the Wisconsin Card Sorting Test (WCST). In complex tasks, executive control may become manifest as decreased flexibility. A simple memory task, the Forward Digit Span Test, was used as a control measure. This test examines immediate attention span or the ability to hold information in mind, which is thought to be a relatively automatic process. The Forward Digit Span Test was used as a control measure, because it was assumed that performance on this measure would not be affected by fatigue. There were 30 individuals in the organically compromised group, with 15 individuals having been subjected to a fatigue condition and 15 having been subjected to a non-fatigue condition. There were 30 individuals in the organically uncompromised group, again with 15 individuals having been subjected to a fatigue condition and 15 individuals having been subjected to a non-fatigue condition. Thus, a control group of healthy individuals with no history of traumatic brain injury was included, adding to the power of the study. Fatigue was induced through working for two hours on a range of cognitively demanding neuropsychological tasks. Fatigue was investigated through the use of a subjective, self-report fatigue rating scale, the Visual Analogue Scale of Fatigue. The results of this study showed that compared to non-fatigued participants, fatigued participants displayed more perseveration and reduced inductive reasoning on the WCST. This trend was consistent in both organically compromised and uncompromised individuals. Fatigue also affected performance on the simple memory task. These findings indicate compromised executive control under fatigue, which may explain the typical errors and sub-optimal performance that are often found in fatigued people. These findings also imply that not only executive control is affected; more automatic processes, such as the ability to hold information in mind also appear to be affected by fatigue. This study adds important information regarding the mechanisms and implications of fatigue on cognitive functioning.